Springbok: An App deployment accelerator for Android smart devices. (October 2018) - Li, Shaoyong; Liu, Yaping; Liu, Zhihong; Hu, Ning
Abstract: Mobile smart devices with Android OS have been widely used in recent years. Developers worldwide are building various complex Apps that require increasing resources and energy. However, as the installation process becomes longer, users must wait for more time before using a new App or upgrading an old one. To address this issue, we propose Springbok, a system that speeds up App deployment for Android devices. By placing the final optimized target file into the Android Package, Springbok directly skips the optimization task, which is the most time-consuming and energy-consuming operation in the installation process. Finally, we implement Springbok and evaluate it with different Android devices. The experimental results show that, in our experimental environment where the WiFi access rate is 65Mbps, Springbok can save time and energy consumption by up to 81% and 86%, respectively.